Degradation of cationized low density lipoprotein and regulation of cholesterol metabolism in homozygous familial hypercholesterolemia fibroblasts. - Basu, S K (1976)
Cultured fibroblasts derived from patients with homozygous familial hypercholesterolemia, which lack functional low density lipoprotein (LDL) receptors, fail to bind, take up, or degrade the lipoprotein with high affinity; therefore LDL-cholesterol is not made available for suppression of cholesterol synthesis or activation of cholesteryl ester formation. When LDL was given a positive charge by reaction with N,N-dimethyl-1,3-propanediamine (cationized LDL), the rate of degradation of the lipoprotein was increased by more than 100-fold in the homozygous familial hypercholesterolemia fibroblasts. Degradation of cationized LDL was inhibited by chloroquine, suggesting that it occurred in cellular lysosomes. Although the cationized LDL entered the cell through a mechanism independent of the LDL receptor, the cholesterol liberated from the degradation of the lipoprotein became available for suppression of cholesterol synthesis and stimulation of cholesteryl ester formation in the homozygous familial hypercholesterolemia fibroblasts. The rate of degradation of albumin by fibroblasts was also increased by more than 100-fold when this protein was coupled to N,N-dimethyl-1,3-propanediamine. The ability to deliver a protein to lysosomes by giving it a strong positive charge may have potential relevance not only to familial hypercholesterolemia, but also to inborn errors of metabolism that involve deficiencies in lysosomal enzymes.